2017
DOI: 10.1039/c6nj03751h
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented β-manno type thiodisaccharides with a C-glycosylic function by photoinitiated hydrothiolation of 1-C-substituted glycals

Abstract: Unique thiodisaccharides of β-manno type featuring C-glycosylic structure with an anomeric functional group for further elaboration were obtained by radical-mediated hydrothiolation of 1-C-acceptor-substituted glycals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…The photoinduced thiol‐ene additions of unsubstituted and 1‐substituted glycals enabled regio‐ and stereoselective synthesis of 2‐thio‐linked saccharide mimetics (Scheme and Scheme ) …”
Section: Photoinduced Hydrothiolation Of Glycals and 1‐substituted Glmentioning
confidence: 99%
See 1 more Smart Citation
“…The photoinduced thiol‐ene additions of unsubstituted and 1‐substituted glycals enabled regio‐ and stereoselective synthesis of 2‐thio‐linked saccharide mimetics (Scheme and Scheme ) …”
Section: Photoinduced Hydrothiolation Of Glycals and 1‐substituted Glmentioning
confidence: 99%
“…Somsák's group reported that the free‐radical hydrothiolation of amide‐, methoxycarbonyl‐ and cyano‐substituted glycal derivatives (e.g. 88 – 91 ) took place with full regio‐ and stereoselectivity due to the preferential axial attack of the thiyl radical to the less substituted C2 position of the pyranose ring and the preferred axial attack on the C1 radical in the hydrogen abstraction step (Scheme ) …”
Section: Photoinduced Hydrothiolation Of Glycals and 1‐substituted Glmentioning
confidence: 99%
“…The radical-mediated addition of thiols to non-activated double bonds is widely used in organic syntheses, material sciences, and glycochemistry as a robust ligation tool [23][24][25][26]. Recent results have demonstrated that applying unsaturated sugars as the alkene partners in the thiol-ene coupling reactions offers a rapid route to a broad range of thio-linked glycomimetics, including 1,2-cis α-S-glycosides [27][28][29][30][31], 2-thio-β-mannosides [32] as well as C-S-bonded carbohydrate mimetics, wherein the CH 2 -S linkage is attached to the C1 or the C5 position of the pyranosyl ring [33][34][35] (Scheme 1B). Dondoni and co-workers reported that, while photoinduced hydrothiolation of 5-exomethylene pyranoside 1 with 1-thioaldose 2a furnished the corresponding S-linked disaccharide 3 with complete regio-and stereoselectivity, addition reaction to galactopyranosyl 5-exomethylene 4 occured with only moderate stereoselectivity, yielding a 3:1 mixture of 5a and 5b (Scheme 1(B1)) [33].…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorus-centered radicals have been less intensively studied in carbohydrate chemistry, but addition products can be used for further transformations. On the other hand, the addition of sulfur-centered radicals to glycals has become very attractive for the synthesis of thio-disaccharides [68][69][70][71][72]. Photochemical initiators based on ketones have been developed for The addition of thiols by radical chain reactions to the 2-position of glycals has only one disadvantage: that the 1-position is reduced under the reaction conditions.…”
Section: Summary and Perspectivesmentioning
confidence: 99%